Development cooperation in a fractured global order : an arduous transition - Sagasti, Francisco R. (International Development Research Centre, 1999)
This book traces the evolution of development cooperation to its impending doom, examines the main trends and changes in the international environment, and explores the future of international development assistance. It will surely stimulate discussion and debate amongst policymakers, academics, practitioners, and students of development worldwide.